Efficient quantum memory of orbital angular momentum qubits in cold atoms. (20th July 2021) - Wang, Chengyuan; Yu, Ya; Chen, Yun; Cao, Mingtao; Wang, Jinwen; Yang, Xin; Qiu, Shuwei; Wei, Dong; Gao, Hong; Li, Fuli
Abstract: The spatial modes of light, carrying a quantized amount of orbital angular momentum (OAM), is one of the excellent candidates that provides access to high-dimensional quantum states, which essentially makes it promising towards building high-dimensional quantum networks. Quantum memory with efficiency above 50% is an essential condition for beating the no-cloning limit or in the one-way quantum computation. However, up till now, the highest storage efficiencies achieved for OAM states are below 30%, which is an obstacle towards practical applications. In this paper, we report the storage and retrieval of photonic qubits encoded with OAM state in an elongated cold rubidium atomic ensemble, achieving a storage efficiency around 65% with an average conditional fidelity above 98%. Our work constitutes an efficient node that is needed towards high dimensional and large scale quantum networks.